Narrative Research of Chemistry Lecturer Career Journey: Challengs, Achievements, Scientific Contribution and The Value of Succes - Sulistina, Oktavia; Lailiyah, Nurul Wahyuni; Chairunnisa, Saskia; Rahayu, Sri (Universitas Negeri Malang, 2023)
The experience of a chemistry lecturer includes a variety of pedagogical and research activities. This study uses a qualitative method with a narrative approach to explore the story and the views of chemistry lecturers on the experience and also the meaning contained in it. The results of this study show that many scientific contributions have been made by chemistry lecturers including cooperation with universities abroad in the development of science and research as well as collaborative research and publications, to the appointment of post-doctoral fellows. The education system in Indonesia is also one of the big challenges that is of particular concern to achieve better education. From the experience of his career journey, there are values of success that have been the main capital in carrying out his responsibilities as a lecturer and professor, including sincerity, honesty, and sincerity.